Digital Literacy, Trust and Perceived Security of the E-government Services: A Case study of Higher Education Students - Leeladharan, M.; Sarin, M. S. (Journal of Information and Knowledge, 2025)
Government systems depend on information and communication technology for expected support, but their efficiency hinges on the willingness and capability of individuals to utilise these systems. The study investigates the Digital Literacy (DL) skills and trust, perceived security of the E-Government (EG) services among higher education students in India. Through an online survey, we explored the impact of DL on trust and perceived security within E-Government services. The study highlights how user’s skill in digital literacy affects their trust levels in E-Government platforms and their perceptions of security regarding data privacy and security. The findings of the research reveal a statistically significant positive correlation (r = 0.117, p < 0.05). This indicates that an increase in digital literacy skills is associated with a corresponding increase in perceived security in e-government, although the strength of this association is moderate. The study provides significant insights into the relationship among Digital Literacy (DL), trust, and perceived security within the context of e-government services. These findings hold implications for policymakers and practitioners interested in advancing digital governance policies.